The electromagnetic response of a superconducting ferromagnets - Leviev, Grigory I.; Tsindlekht, Menachem I.; Sonin, Edouard B.; Felner, Israel (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The electromagnetic response of the superconducting ferromagnets RuSr2Gd1.5 Ce0.5Cu2O10 (Ru–1222 Gd) in an ac magnetic field of finite amplitude is investigated. Taking into account weak links between granules and magnetization of the magnetic sublattice, it is shown that the response of a sample in a superconducting state with the fundamental frequency and frequency of the 3rd harmonic can be described by the nonlinear equation for the macroscopic field. Generation of the harmonic at temperatures above superconducting transition corresponds to Rayleigh`s mechanism. Using various regimes of a sample cooling, the internal magnetic field determined by the magnetic sublattice was measured. This is direct evidence of the coexistence of ferromagnetic and superconductive order parameters in high-Tc ruthenocuprates.